Climate-Induced Disaster in Nepal: Assessing Impact of Glacial Lake Outburst Floods in Thame Valley, Solukhumbu - Pasa, Rajan Binayek; Rai, Suman; Adhikari, Devendra (Nepalese Journal of Development and Rural Studies, 2024)
Nepal’s Himalayan region is always prone to the Glacial Lake Outburst Floods (GLOFs), which is mainly caused due to climate change. In Nepal’s Thame Valley, the 2024 GLOF caused massive destruction, including the loss of infrastructure, farmland, and natural landscape that has negatively impacted to the community’s economy. The purpose of this study is to investigate the socioeconomic and environmental effects of the Thame GLOF, applying Key Informant Interviews methods in which participants are locals, local government officials, and business owners, and others. We found that there is a damage to tourism infrastructure, agriculture, and essential facilities, due to the community has faced severe economic loss. Socially, there exists flood related traumas amongst children, locals are worried about the loss of property, and they have expressed concerns about inadequate early warning systems and awareness programs. Local government’s role is found key to manage these type of climate-induced disaster. The environmental aspects highlight the destruction of natural landscape, loss of agriculture land, drinking water contamination, and risk of other GLOFs in the study area due to global warming. These high-altitude settlements need the United Nations Loss and Damage fund to implement mitigation and adaptation strategies for climate-induced disasters. The study concludes that Himalayan settlements are always at potential risks of such disasters due to climate change, so it is urgent to initiate integrated mitigation strategies, and ensure sustainable- adaption measures in these high-risks areas. This research is useful for academicians, policy makers, and climate advocates to prepare evidence-based policies related to climate change, and lobby to develop safer Himalayan communities.